Endophytic bacteria producing antibacterial against methicillinresistant Staphylococcus aureus (MRSA) in seagrass from Rote Ndao, East Nusa Tenggara, Indonesia - DIAN SAGITA FITRI; ARTINI PANGASTUTI; ARI SUSILOWATI; SUTARNO SUTARNO (Society for Indonesian Biodiversity, 2017)
Fitri DS, Pangastuti A, Susilowati A, Sutarno. 2017. Endophytic bacteria producing antibacterial against methicillin-resistant Staphylococcus aureus (MRSA) in seagrass from Rote Ndao, East Nusa Tenggara, Indonesia. Biodiversitas 18: 733-740. Methicillinresistant Staphylococcus aureus (MRSA) are bacteria that resistant to the various type of antibiotics and yet cannot be handled comprehensively. The discovery of new antibiotic from endophytic bacteria in seagrass of Rote Island is an option to overcome the resistance. The aims of this research were to screen endophytic bacteria inhibit MRSA from seagrass, to determine the species of the endophytic bacteria and the genetic relationship. Isolation of endophytic bacteria has carried out by inoculating surface sterilization seagrass leaves on Marine Agar (MA) medium. Selection of potential endophytic bacteria-producing anti-MRSA has done using overlay method against MRSA, gram-positive Bacillus subtilis, and gram-negative Escherichia coli. Identification of the endophytic bacteria based on the sequence of 16S rRNA encoding gene. The results showed that there were eight isolates of endophytic bacteria which have antibacterial activity against MRSA of seagrass Enhalus acoroides, Thalassia hemprichii, and Cymodocea rotundata in the Litianak and Oeseli Beaches, Rote Ndao. The diameter of inhibition zone was between 0.65-18.27 mm with narrow spectrum with broad spectrum antibacterial activity. The eight potential endophytic bacteria identity were Bacillaceae E2M1, Bacillaceae E2M3, Bacillus E2M4, Bacillus E2M7, Bacillaceae E2M8, Pseudomonadaceae C1M7, Shewanellaceae C2M3, and Rhodobacteraceae T1M3. Most of the isolates can be said to be a new species as the percent similarity of 16S rRNA gene sequence was less than 95% and promising to produce new antibacterial compounds. Phylogenetic relationship showed some isolates clustering in different groups that present the diverse groups of endophytic bacteria were found.